Antifungal Efficacy and Safety of Cycloheximide as a Supplement in Optisol-GS - Dal Pizzol M; Freitas EC; Locatelli C; Guareze F; Reginatto P; Machado G; Fuentefria A; Marinho D (Dove Medical Press, 2021)
Melissa Dal Pizzol,1,2 Eduarda Correa Freitas,2 Claudete Locatelli,2 Felipe Guareze,2 Paula Reginatto,3 Gabriella Machado,3 Alexandre Fuentefria,3 Diane Marinho1,2 1Programa de Pós-Graduação em Medicina: Ciências Cirúrgicas, Universidade Federal do Rio Grande do Sul, Porto Alegre, Brazil; 2Ophthalmology Department, Hospital De Clínicas De Porto Alegre, Porto Alegre, Brazil; 3Programa de Pós-Graduação em Ciências Farmacêuticas, Faculdade de Farmácia, Universidade Federal do Rio Grande do Sul, Porto Alegre, BrazilCorrespondence: Melissa Dal PizzolOphthalmology Department, Hospital de Clínicas de Porto Alegre, Rua Ramiro Barcelos, 2350, Zona 17, Porto Alegre, CEP 90035-903, RS, BrazilTel +55 5133598306Email melissadalpizzol@hotmail.comPurpose: The incidence of fungal infection after corneal transplant has increased significantly in recent years, especially Candida spp. This study aimed to evaluate the efficacy and safety of the addition of cycloheximide in Optisol-GS media in decreasing the growth of Candida spp. strains.Methods: This in vitro laboratory efficacy study measured fungal colony growth in 24 vials of Optisol-GS that were divided into 6 groups of 4 vials each, as follows: (1) MIC/2 cycloheximide, (2) MIC cycloheximide, (3) MICx5 cycloheximide, (4) MICx10 cycloheximide, from MIC values obtained for each strain, (5) unsupplemented optisol-GS as a positive control (added inoculum), and (6) unsupplemented optisol-GS as a negative control (no inoculum). In each group was added Candida albicans, C. glabrata and C. parapsilosis, except in the negative control. The evaluated variables were fungal colony growth from the Optisol-GS vials, corneal endothelial cell density and endothelial cell viability at different concentrations of cycloheximide.Results: In the efficacy study, all strains showed a reduction in fungal cell growth from the second day at all evaluated concentrations of optisol-GS supplemented with cycloheximide, even at subinhibitory concentrations (MIC/2). For C. glabrata, the colony count was reduced to 99%. No evidence of corneal endothelial toxicity was found at any concentration, in the safety study, compared with the paired control.Conclusion: The addition of cycloheximide to optisol-GS decreased the fungal growth, demonstrating fungicide action against C. glabrata and fungistatic action against C. albicans and C.parapsilosis. This drug did not demonstrate toxicity to the corneal endothelium at different concentrations.Keywords: cornea, eye banking, infection, pharmacology